A flora e vegetação da caatinga em São João do Sabugi – RN: uma homepage para construção, valorização e conservação deste bioma - Nóbrega, Fabiana Silva da (2019)
In the course of botany’s classes it has been increasingly more difficult to withhold the attention of the students, and thus, making significant the learning process. According to reports, the exacerbated advance of digital media, in all spaces of coexistence, the scholar one included, along with the traditional and decontextualized way the botany’s classes are being ministered, have been hindering aspects of the knowledge’s construction process. In this context, the challenge to find alternatives to alter this reality is conveyed to the teacher, that must rethink his practices and seek methodological strategies and pedagogical tools that awake the students’ interest and, in the same time, contribute to the construction of a significant learning. In this scenario, in order to develop works that utilize tools that are present in the student’s everyday life, as the use of TICS, have been one of the strategies adopted in order to try to attract the student’s attention during the classes. Henceforward this idea, it has been produced a blog, named: “flora of São João do Sabugi”, with the objective to ease the teaching and the learning about vegetables, as well as develop a feeling of appreciation and conservation of the São João do Sabugi’s caatinga. Analyzing the pretest, it has been noticed that the students had a low level of knowledge about the caatinga’s plants’ diversity, and so it has been adopted the strategy of teaching botany utilizing the elements of the local flora, as a way to promote the rapprochement of the student with his object of study, which is present in his everyday life and, thus far, awakening his interest. After the realization of the interventive actions, dialogued and field classes, and workshop’s development, it was found an increase of the knowledge about the plants’ varieties by the students, fact verified by the greater number of species named in the post test. The presential contact with the plants, that has occurred in loco, in order to capture photographic registers through the using of cellphones, has contributed to raise the knowledge about the approached theme, as well as to present pleasant alternatives to the use of the cellphones, as an educational tool. Therefore, the blog “flora of São João do Sabugi”, being a cooperative work, presents itself as an alternative to work with the botany in a practical and investigative way, whose process of confection offered the students opportunities of participation and socialization of the knowledge in diverse experiences of their everyday life, rappocheing them with the botany’s contents, promoting the socialization of knowledge and the interaction between teacher and students, between themselves, and with themselves and their place of existence, contributing to a dynamical, contextualized and productive learning.